Transformasi Estetika Seni Tari Tradisional dalam Konteks Pertunjukan Modern: Antara Visualitas dan Makna - Wibisono, Namira Allegra (Universitas Jambi, 2026)
Background of this research is the phenomenon of aesthetic transformation of Indonesian traditional dance in the context of modern performances that demand the reinforcement of visuality aspects, yet potentially shift the cultural, spiritual, and symbolic meanings inherent in the dance. Objectives of this research are to analyze the forms of visuality transformation in modern traditional dance performances, to describe the impact of visuality transformation on the meaning of traditional dance, and to map the relationship between visuality and meaning in contemporary performance practices. Methods this research employs a systematic literature review (SLR) with the PRISMA protocol. Data collection was conducted through literature searches on Publish or Perish and Google Scholar databases using the keywords